2021
DOI: 10.1186/s13014-021-01777-7
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate margin for planning target volume for breast radiotherapy during deep inspiration breath-hold by variance component analysis

Abstract: Background This study aimed to quantify errors by using a cine electronic portal imaging device (cine EPID) during deep inspiration breath-hold (DIBH) for left-sided breast cancer and to estimate the planning target volume (PTV) by variance component analysis. Methods This study included 25 consecutive left-sided breast cancer patients treated with whole-breast irradiation (WBI) using DIBH. Breath-holding was performed while monitoring abdominal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Ono et al reported internal and setup margins for breast radiotherapy during deep inspiration breath-hold using the REML formula. 20 They found that the systematic errors of the chest wall motion were smaller than the random errors, and appropriate systematic errors were indicated. In the current study, it was clarified that the appropriate IMs for the prostate were derived from the REML formula by excluding overestimation of systematic errors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ono et al reported internal and setup margins for breast radiotherapy during deep inspiration breath-hold using the REML formula. 20 They found that the systematic errors of the chest wall motion were smaller than the random errors, and appropriate systematic errors were indicated. In the current study, it was clarified that the appropriate IMs for the prostate were derived from the REML formula by excluding overestimation of systematic errors.…”
Section: Discussionmentioning
confidence: 98%
“…Ono et al. evaluated the intra‐fractional and inter‐fractional chest‐wall motions for breast radiotherapy during a deep inspiration breath‐hold, and the planning volume target (PTV) margin was estimated using the REML formula 20 . They found that the PTV margin would be reduced using the REML formula excluding overestimation of systematic errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ono et al. 19 calculated the setup margin for left‐sided breast radiotherapy during DIBH. They found the optimal planning target volume (PTV) margin as 3.59 mm from analyzing the systematic and random errors.…”
Section: Discussionmentioning
confidence: 99%
“…PSNR is the quotient of the medium voltage about the peak omen to the noise [80]. MSE shows the average of the sum of squares of the divergence amid the pixel equivalent of the detected image and the pixel equivalent of the original image [81]. We mark the structural correlation together the detected data with the initial data by SSIM.…”
Section: Edge Detection Evaluation Indexmentioning
confidence: 99%